PELAKSANAAN HYGIENE SANITASI PADA MASA PANDEMI DI HARRIS CAFÉ HARRIS HOTEL BATAM CENTER - Avennia Hutabarat; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tourism is one sector that helps improve the country's economy, tourism provides various tourist activities and service facilities, one of which is restaurants, restaurants as a place for guests to get food and beverage services. In the pandemic era, the implementation of good sanitation hygiene is an effort to maintain trust and satisfy consumers, in addition to having to maintain and pay attention to every quality of the products and services offered. Hygiene sanitation is an effort to create an environment that is healthy, safe, and free from environmental pollution, so as to avoid disease. This study uses qualitative methods with data collection techniques through observation, interviews and documentation. The analytical method used in this study is a qualitative descriptive method. The purpose of this study was to find out how the implementation of hygiene and sanitation, supervision of the implementation of hygiene sanitation and the obstacles and efforts made in the implementation of hygiene sanitation during the pandemic at Harris café HARRIS Hotel Batam Center. The results of the analytical research carried out carried out standard operating procedures for hygiene and sanitation well with strict supervision, several obstacles in the implementation of both personal and food hygiene as well as room and equipment sanitation but can be overcome with several efforts. Keywords : Hygiene, Sanitation, Restaurant